RSV neutralization assays – Use in immune response assessment. Issue 33 (30th July 2021) - Raghunandan, Rama; Higgins, Deborah; Hosken, Nancy
Highlights: RSV neutralization assays are complex biological assays used for measurement of functional antibody responses. A broad variety of RSV neutralization assay formats are currently in use. Use of the 1st International Standard for Antiserum to RSV is necessary to harmonize neutralization assay output across formats. This paper outlines good practices for key assay components and data analysis to promote the quality and consistency of RSV neutralization assay results. Abstract: Respiratory syncytial virus (RSV) is a leading cause of respiratory illness among children and infants worldwide, yet no licensed vaccine exists to reduce the risk of disease. At least 16 RSV vaccine candidates are currently in clinical development and many are designed to induce robust virus neutralizing immune responses. RSV neutralizing antibody (nAb)-mediated interventions such as intravenous immunoglobulin (IVIG) and palivizumab provide passive protection against serious lower respiratory tract disease due to RSV, validating nAbs as a correlate of protection. To identify correlates of protection for vaccine candidates that have demonstrated their protective efficacy, an investigator can use assays designed to measure nAb responses. However, there is no standard method of measurement; individual laboratories have developed their own methods to measure the ability of nAbs to reduce the infectivity of a defined virus dose in a variety of cell lines, leading to establishment of the broad variety of RSV neutralization assay formats currently in use. Standardizing the RSV neutralization assay is an essential step toward better assessment of nAb responses to vaccine candidates. Use of a common reference standard by all makes comparing the immunogenicity of different vaccine candidates feasible. In the context of vaccine development, the WHO 1 st International Standard for Antiserum to RSV (RSV IS) has been shown to be suitable for harmonizing results across laboratories and assay formats used to measure nAb titers to RSV/A and RSV/B in human sera. This review describes the broad variety of RSV virus neutralization assay formats currently in use and the importance of the RSV IS for harmonization of results across formats and across laboratories. It also outlines good practices for key assay components and data analysis to promote the quality and consistency of measuring RSV nAb titers in serum specimens.